Hormonal responses to physical training in high-level peripubertal male gymnasts - Daly, R. M.; Rich, P. A.; Klein, R. (European Journal of Applied Physiology, 1998)
We examined the training-related responses of total testosterone (T), insulin-like growth factor-1 (IGF-1), cortisol (C) and diet in 16 peripubertal (pubertal stage ≤2) male gymnasts. Either the gymnastics training performed by these subjects was not intense enough to alter adrenal function, or that the gymnasts were well adapted to the training. In contrast, the reduction in the anabolic to catabolic balance represented by the IGF-1:C ratio is suggestive of a catabolic state.